PENINGKATAN KADAR SULFUR DAN SELENIUM HIJAUAN Zea mays saccharata OLEH PEMUPUKAN FOSFOR DALAM SUSPENSI FERMENTASI Acetobacter-Saccharomyces SULFUR AND SELENIUM CONTENT IMPROVEMENT OF Zea mays saccharata WITH PHOSPHORUS FERTILIZATION IN THE FERMENTED Acetobacter-Saccharomyces SOLUTION - Lukiwati, Dwi Retno; Nurhidayat, Novik; Winarbie, Saputro Hari (Pembangunan Pedesaan, 2006)
A greenhouse experiment was conducted during 6 weeks on acid latosolic soil and low phosphorus availability. A completely randomized design with 5 treatments and 4 replicates was used. The treatments were control, RP, SP, RP+FSAS, and SP+FSAS. Phosphorus fertilizer level was 200 kg P2O5/ha (2.96 g RP/pot or 2.22 g SP/pot). Sweet corn was cut and measured for S and Se content on 6 weeks after planting. All data were analyzed by the GLM procedure of SAS. Significant differences among the treatments were calculated by DMRT. The results show that SP+FSAS increased S and Se content significantly higher compared to control and RP (P